Re-Reading the Gospel in Africa: A Theological Discourse with Albert Nolan and Jean-Marc Éla (Hekima Review, 2025)
Africa faces many challenges regarding better livelihood, peace, prosperity, human well-being, and dignity. The protractedconflicts over land and natural resources, coups d’état, and the perpetuating systems of oppression that deny the economic and political agency of the people, along with scarce opportunities for prospects within the continent, aggravate the already existing plight of Africans. The message of the Gospel confronts these miseries of Africans daily. However, Christian theologising in Africa often grapples with the challenge of being distant and disconnected from the daily realities of Africans. While neglecting the present and people’s lived experience, theology exclusively seeks other-worldly salvation only directed toward a future. The paper proposes re-reading the Gospel in Africa inspired by Jesus’ spirituality, which is hope-filled, contextual, liberating, and transformative. Albert Nolan’s and Jean-Marc Éla’s theological contributions shape this exploration of Christian theology that is both African and Jesus-centred. It is a spirituality centred on hope, shaped by the existential plight of Africa while proposing a liberating agency andimpetus for a socio-spiritual transformation.